2013
DOI: 10.1016/j.neuroimage.2013.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Processing counterfactual and hypothetical conditionals: An fMRI investigation

Abstract: Counterfactual thinking is ubiquitous in everyday life and an important aspect of cognition and emotion. Although counterfactual thought has been argued to differ from processing factual or hypothetical information, imaging data which elucidate these differences on a neural level are still scarce. We investigated the neural correlates of processing counterfactual sentences under visual and aural presentation. We compared conditionals in subjunctive mood which explicitly contradicted previously presented facts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Interestingly, Kulakova et al (2013) found involvement of one core DN region (right cuneus) with an activation peak that was almost identical to our finding in LV1 for the person-based > object-based contrast. In their study, Kulakova and collaborators had participants semantically evaluate hypothetical and counterfactual sentences presented either visually or aurally.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, Kulakova et al (2013) found involvement of one core DN region (right cuneus) with an activation peak that was almost identical to our finding in LV1 for the person-based > object-based contrast. In their study, Kulakova and collaborators had participants semantically evaluate hypothetical and counterfactual sentences presented either visually or aurally.…”
Section: Discussionsupporting
confidence: 89%
“…Given recent neuroimaging results showing significant overlap in DN regions during episodic memory and theory of mind tasks (Spreng & Grady, 2010; Mitchell, 2009), and greater involvement of DN during simulations that involve primarily autobiographical details rather than tasks involving non-autobiographical processing of objects (Addis, Wong, & Schacter, 2007, Addis et al, 2009; Hassabis et al, 2007), we expected to see greater involvement of DN during person-based (i.e., self and other) relative to object-based counterfactual simulations. Indeed, two recent fMRI studies exploring neural correlates of semantic evaluation of non-autobiographical hypothetical and counterfactual statements show relatively little involvement of DN regions (Nieuwland, 2012; Kulakova et al, 2013), further suggesting that object-based counterfactual simulations may primarily recruit processes outside the DN.…”
Section: Introductionmentioning
confidence: 99%
“…Here is the resulting status of each case in the partition for a true counterfactual conditional, If Mary had had pneumonia then she would have been ill: The mental models are more parsimonious. They represent the fact, not-A and not-B, and its corresponding counterfactual possibility, A and B-as is borne out in studies of reasoning (Byrne, 2002(Byrne, , 2005(Byrne, , 2016) and a brain imaging study (Kulakova, Aichhorn, Schurz, Kronbichler, & Perner, 2013). A false counterfactual, such as:…”
Section: Factual and Counterfactual Conditionalsmentioning
confidence: 99%
“…The prevalent involvement of the right hemisphere was further supported by an fMRI study by Kulakova et al (2013). Factual sentences (The motor is switched off today) were followed by either a counterfactual conditional that explicitly contradicted the presented facts (If the motor had been switched on today, would it have burned fuel?)…”
Section: Functional Neuroimaging Of Counterfactual Sentence Comprehenmentioning
confidence: 87%